Stories from Poland by a Welsh Soldier–John Elwyn Jones’s Translations - Klonowska, Marta (Studia Celtica Posnaniensia, 2016)
The majority of translations from Polish into Welsh published so far are the works of John Elwyn Jones (1921-2008), who learned Polish in a German prisoner-of-war camp during World War II. His translations include Storiâu Byr o’r Bwyleg, a collection of short stories by two of the classic authors of the Polish Positivist period, Bolesław Prus and Henryk Sienkiewicz. This paper analyses two stories from the collection, Ianco’r Cerddor “Janko Muzykant” and Y Wasgod “Kamizelka”, within a comparative functional model of translation criticism. The texts are analysed in the light of lexical-semantic, cultural and aesthetic codes. A great number of modifications to the source texts introduced in the Welsh translation places them on the border between free translations and adaptations. While some of the alterations are tokens of a specific translation strategy, others can be regarded as translation errors. Although the Welsh version retains the primary message of the original stories, much of their culture-specific dimension, historical context and artistic value is not conveyed in the translation.